Alcohol Consumption Enhances Vection. (May 2013) - Seno, Takeharu; Nakamura, Shinji
We assessed changes in forward vection following alcohol consumption, and found that alcohol consumption enhanced vection. This result indicates that alcohol can affect psychophysical processes responsible for self-motion perception.